ChemInform Abstract: Ligand‐Free Pd‐Catalyzed and Copper‐Assisted C—H Arylation of Quinazolin‐4‐ones with Aryl Iodides under Microwave Heating. Issue 33 (August 2015) - Laclef, Sylvain; Harari, Marine; Godeau, Julien; Schmitz‐Afonso, Isabelle; Bischoff, Laurent; Hoarau, Christophe; Levacher, Vincent; Fruit, Corinne; Besson, Thierry
Abstract Several quinazolin‐4‐ones and pyrido‐pyrimidin‐4‐one derivatives thereof are transformed according to the title reaction.